Coronary sinus reducer transfemoral extraction after intraprocedural device migration: A case report. Issue 1 (24th November 2020) - Bunc, Matjaz; Sustersic, Miha; Langel, Crt; Kuhelj, Dimitrij; Banai, Shmuel
Abstract: The coronary sinus reducer migration during implantation procedure is a rare complication with no standard bailout strategy. Transfemoral extraction of the reducer can be a safe and successful method, as demonstrated by this case report. Abstract : The coronary sinus reducer migration during implantation procedure is a rare complication with no standard bailout strategy. Transfemoral extraction of the reducer can be a safe and successful method, as demonstrated by this case report.